1989
DOI: 10.1136/thx.44.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hydatid cysts of the lung: report on 1055 patients.

Abstract: Of 1055 patients treated surgically for pulmonary hydatid disease, most (950) had isolated lung cysts, the other 105 having both liver and lung cysts. The chest radiograph was most valuable in diagnosis; the Casoni and Weinberg tests and blood eosinophil counts were found to be diagnostically unreliable. One thousand and seventy seven primary operations were performed. Cystotomy and capitonnage were carried out in 906 patients, 40 of whom also had decortication of the pleura. Other procedures included cystotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
270
6
41

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(339 citation statements)
references
References 10 publications
22
270
6
41
Order By: Relevance
“…Rupture of the hydatid cyst may be manifested by vigorous coughing and expectoration of membranes (5,6,15). No history of previous dyspnea or any other symptom relating to the hydatid cyst was present in the case presented here.…”
Section: Discussionmentioning
confidence: 78%
“…Rupture of the hydatid cyst may be manifested by vigorous coughing and expectoration of membranes (5,6,15). No history of previous dyspnea or any other symptom relating to the hydatid cyst was present in the case presented here.…”
Section: Discussionmentioning
confidence: 78%
“…Dogan et al, in their series with 1055 cases, reported that cysts were located on the right in 60%, and on the left in 38% [16]. Additionally, in 2% of patients, cysts were located in both lungs, and in 7%, multiple lung cysts existed.…”
Section: Discussionmentioning
confidence: 99%
“…If right lung hydatid cyst accompanying liver hydatid cyst exist, thoracic diaphragmatic approach is applied. The preferred method of bilateral lung cysts is single-stage median sternotomy or two-stage thoracotomy, in which larger cysts are operated first [16]. Medical treatment is recommended for patients for whom surgical approach is not deemed appropriate, who have major vascular involvements, and many small cysts involving one or more organs [21].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic and/or therapeutic use of invasive techniques and interventional radiological procedures carries the risk of puncturing cysts, and this could lead to anaphylactic reaction, formation of secondary cysts, or even sudden death. [6,8] Though successful results have been reported with mebendazole and albendazole, surgical therapy is still the most favored method for treating hydatid cysts. Some authors have suggested using albendazole as a supportive therapy for surgery in order to decrease the incidence of recurrence.…”
Section: Discussionmentioning
confidence: 99%